Економічний вимір конституції - Пустовалова, Інна Сергіївна; Pustovalova, I. S. (Харків : Харківський національний університет імені В.Н. Каразіна, 2024)
У роботі охарактеризовано конституцію як установчий документ щодо економічної системи суспільства, розкрито роль і значення конституції як регулятора економічної політики держави, з’ясовано особливості конституції як нормативної основи забезпечення економічної безпеки. Розкрито потенціал сучасних конституцій щодо нормативного забезпечення економічної безпеки держави; визначено основні напрями забезпечення економічної безпеки на рівні основного закону; доведено, що протягом останніх десятиліть одним із пріоритетів конституційного захисту економічної безпеки стало запобігання корупції. Скориговано наукові погляди на видове розмаїття конституційних прав і свобод людини і громадянина. У результаті проведеного дослідження набули подальшого розвитку наукові погляди на видове розмаїття і функціональну роль конституційних норм; розкрито специфіку структурування установчих норм, що стосуються економічної системи, в тексті основного закону. Сформульовано низку пропозицій щодо посилення економічного виміру чинної Конституції України.

The work characterizes the constitution as a founding document regarding the economic system of society, reveals the role and significance of the constitution as a regulator of the state's economic policy, elucidates the peculiarities of the constitution as a normative basis for ensuring economic security. The potential of modern constitutions regarding regulatory provision of economic security of the state is revealed; the main areas of ensuring economic security at the level of the basic law are defined; it is proved that during the last decades, one of the priorities of the constitutional protection of economic security has become the prevention of corruption. Scientific views on the various types of constitutional rights and freedoms of a person and a citizen have been adjusted. As a result of the conducted research, scientific views on the types of diversity and the functional role of constitutional norms gained further development; the specifics of the structuring of the constituent norms relating to the economic system in the text of the basic law are disclosed. A number of proposals on strengthening the economic dimension of the current Constitution of Ukraine have been formulated.
Economic dimension of the constitution
Keywords: конституція; конституціоналізм; конституційний лад; конституційна економіка; засади конституційного ладу; громадянське суспільство; права людини; економічні права і свободи людини; constitution; constitutionalism; constitutional order; constitutional economy; principles of constitutional order; civil society; human rights; economic human rights and freedoms